Asap Cair Sebagai Pengawet Alami pada Bandeng Presto - Sih Yuwanti (agriTECH, 2005)
"Bandeng presto" is easily spoilage at room temperature. Liquid smoke has properties as antimicrobial and antioxidant, so liquid smoke can act as a natural preservative. The objective of this study was to evaluate the antimicrobial and antioxidant activities of liquid smoke on "bandeng presto". Three concentrations of liquid smoke (2.5%, 5% and 7.5%) together with 25% salt solution was used in immersing bandeng before being cooked under pressure, control was immersed only in salt solution. The result showed that liquid smoke was able to retard the growth of microbial and lipid oxidation on "bandeng presto". The ability of liquid smoke as antimicrobial and antioxidant on "bandeng presto" increased as the increasing of liquid smoke concentration. Liquid smoke of 7.5% prolonged the shelf life of "bandeng presto" from I day to 6 days at room temperature and from 21 days to more than 28 days at cold temperature.